THE VALUE OF CHARACTER EDUCATION IN THE STORY OF THE GARUDA IN ADIPARWA TEXT - I Made Sujanayasa; Dewa Komang Tantra; I Made Surada; I Nyoman Subagia; I Gede Suwantana (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2022)
Character values in Hinduism contain many lessons about ethics, morals and manners.  The educational system could be found, for example, in the Adiparwa text, which is a part of the Mahabharata that tells about the birth of The Garuda, how he saved his mother from slavery and eventually became Lord Vishnu's mount.  In this Adiparwa, there is an interesting part of The Garuda's story.  Through this literature study, a narrative about the Garuda was obtained which was then made into a short story in the form of a synopsis.  Based on the research, the setting could be found in the story includes time and places where the story took place.  By this literature search, the characters of and in The Garuda story could also be formulated.  Based on the writing, five characters of education are found, which are reflected in the story that tells the students (The Kadru, The Winata, the dragons, The Garuda and Lord Vishnu). As for the character education in question, its botom lines are as follows: religious, honest, disciplined, hard working and responsible.